Embryo development of the deep-sea octocoral Dentomuricea aff. meteor from the Azores under two temperature regimes - Maria Rakka; António Godinho; Covadonga Orejas; Marina Carreiro-Silva (PANGAEA, 2022)
Includes data on the embryo development of the species. Embryos/larvae were monitored (counted) and classified to developmental stages every 3-4 hours until the planula stage and every 2-3 days afterwards.
In: Rakka, M et al. (2022): Embryo and larval biology of the deep-sea octocoral Dentomuricea aff. meteor from the Azores under two temperature regimes [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.942769